Center-Pivot-Irrigated Confectionary Sunflowers Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on production of center-pivot-irrigated confectionary sunflowers in western Kansas.
MF938_1999_10
Keywords: MF938; Economics; Crops; MF